An analysis of the factors affecting entrepreneurial intention : evidence from Turkey - Yukarıpınar, Sevde Nur (My University, 2020)
ÖZETGİRİŞİMCİLİK YÖNELİMİNİ ETKİLEYEN BİR ARAŞTIRMA:TÜRKİYE ÖRNEĞİSon yüzyıllarda, gelişmiş ve gelişmekte olan ülkelerde girişimciliğe verilen önem giderek artmaktadır. Bu durumun temel nedeni ise, girişimciliğin ekonomik kalkınma ve gelişime olan büyük katkısının ve işsizlik sorununa önemli ölçüde çözüm oluşunun fark edilmesidir. Bu doğrultuda, devletler ekonomik kalkınmayı arttırmak ve devam ettirmek, var olan işsizlik sorununu çözmek amacıyla girişimcileri destekleme ve potansiyel girişimcileri ortaya çıkarma politikaları ve programları geliştirmektedirler. Türkiye’de girişimciliğe verilen önemle birlikte girişimcilik eğitimi son dönemlerde artarak özellikle üniversitelerin ilgili bölümlerinde ders olarak okutulmaya başlanmıştır ve verilen derslerin öğrencilerin girişimcilik niyetine olan etkisi önemli ölçüde araştırma konusu olmuştur. Ancak yalnızca, girişimcilik dersi alan üniversite öğrencileri değil her yaştan, her meslekten, her gruptan kişilerin çeşitli alanlarda girişimciliğe olan yönelimini görmekteyiz. Bu kişiler ailemizden, akrabalarımızdan, yakın arkadaşlarımızdan ve ya yakın çevremizden birileri olabilir. Bu sebeple bu araştırmada, sadece öğrenciler değil, Türkiye’de +18 yaş ve üzeri her kesimden 403 kişinin girişimcilik yönelimini etkileyen faktörler ve bu faktörlerin arasındaki ilişki incelenmiştir. Araştırmamızda, Shapero ve Sokol’un (1982) Girişimcilik Olayı Modeli ve bu modelin daha kapsamlı hali olarak görülen Ajzen’in (1991) Planlanmış Davranışlar Teorisi birleştirilmiş ve girişimcilik eğitimi unsuru da dahil edilerek girişimcilik yönelimini etkileyen faktörlerin regresyon analizleri yapılmıştır. Araştırma bulgularına göre, Ajzen’in Planlanmış Davranışlar Teorisine göre kişisel tutum bağlamında girişimci olma cazibesi, sosyal norm bağlamında girişimcilik kariyerine bakış, girişimci olmanın onaylanması ve girişimcilik kültürü, algılanan davranış kontrolü bağlamında kişisel yeterlilik faktörleri girişimcilik yönelimi ile anlamlı ve ilişkili bulunmuştur. Girişimcilik eğitimi faktörlerinin ise girişimcilik yönelimi ile doğrusal regresyonda ilişkisi bulunurken çoklu regresyonda ilişkisi bulunamamıştır. Bu sebeple, eğitimin ayrıca kişisel tutum ve algılanan davranış kontrolü, ve sosyal normlar ile ilişkisi araştırılmıştır. Elde edilen sonuçlara gore gririşimcilik eğitiminin kişisel tutum bağlamında girişimci olma cazibesi ile ilişkisi ve çalışan olma cazibesi ile yüksek oranda ilişkisi, sosyal norm bağlamında girişimcilik kariyerine bakış ve girişimci olmanın onaylanması ile ilişkisi, algılanan davranış kontrolü bağlamında kişisel yeterlilik ve kişisel beceri ile ilişkisi bulunmuştur.TABLE OF CONTENTSÖZETiABSTRACTiiiACKNOWLEDGEMENTSvLIST OF TABLESviiiLIST OF FIGURESxiABBREVATIONSxii1. INTRODUCTION11.1. Definition of Core Concept11.2. The Importance of Entrepreneurship21.3. Need for Research21.4. The Purpose of The Study31.5. Organization of Dissertation32. LITERATURE REVIEW42.1. The Definitions and Historical Development of Entrepreneurship42.2. Entrepreneurship in Turkey72.3. Entrepreneurial Intention92.4. Factors Affecting Entrepreneurial Intention102.4.1. Demographic Factors102.4.2. Psychological Characteristics132.4.3. Entrepreneurship Education152.4.4. Entrepreneurial Intention Models172.5. Research on Entrepreneurial Intention233. METHODOLOGY AND RESEARH DESIGN323.1. The Scope of The Research323.2 The Proposed Theoretical Research Model333.3. Research Questions343.4. Sample and Data Collection344. RESEARCH AND FINDINGS374.1. Reliability and Factor Analyses374.1.1. Reliability and Factor Analysis of Attitude Toward Behavior384.1.2. Reliability and Factor Analysis of Subjective Norms414.1.3. Reliability and Factor Analysis of Perceived Behavioral Control434.1.4. Reliability and Factor Analysis of Entrepreneurship Education464.1.5. Reliability and Factor Analysis of Entrepreneurial Intention484.2. Revised Model and Hypotheses After the Reliability and Factor Analyses514.3. Correlation and Simple Linear Regression Analyses534.4. Correlations and Multiple Regression Analyses644.5. Independent t-Test Analyses of Demographic Data694.6. ANOVA Analyses of Demographic Data724.7. Results834.7.1. Results of Factor and Reliability Analyses834.7.2. Results of The Simple Linear Regression for Entrepreneurial Intention844.7.3. Results of The Simple Linear Regression for The Effect of Entrepreneurship Education854.7.4. Results of Multiple Linear Regression for Entrepreneurial Intention864.7.5. Results of Independent t-Tests for Entrepreneurial Intention864.7.6. Results of ANOVA Tests for Entrepreneurial Intention875. DISCUSSIONS AND CONCLUSIONS885.1. Discussions and Implications885.2. Conclusion935.3. Limitations935.4. Recommendations946. REFERENCES95APPENDIX: QUESTIONNAIRE104

In recent centuries, the importance given to entrepreneurship is increasing in developed and developing countries. The main reason for this situation is the realization of the great contribution of entrepreneurship to economic development and a significant solution to the unemployment problem. In this direction, states develop policies and programs to support entrepreneurs and unearth potential entrepreneurs in order to increase and maintain economic development and solve the existing unemployment problem.Turkey has also started to be given in the relevant section of entrepreneurship education courses in universities. The effect of courses on entrepreneurship education on students' entrepreneurial intention has been a significant research topic. However, we see not only university students taking entrepreneurship courses, but also people of all ages, professions and groups towards entrepreneurship in various fields. These people may be members of our family, relatives, close friends or our immediate environment. For this reason, not only the entrepreneurial intention of the students was investigated in this study. In our research data, not just students, were obtained from people who are over the age of +18 in Turkey. Factors affecting entrepreneurial intention were investigated with the obtained data and the relationship between these factors was examined.In our analysis, the Entrepreneurship Event Model of Shapero and Sokol (1982) and Ajzen's (1991) Planned Behavior Theory, which is seen as a more comprehensive version of this model, were combined and regression analysis of the factors affecting entrepreneurship intention was made by including the entrepreneurial education element.According to the findings of the research, according to Ajzen's Theory of Planned Behaviors, the attraction to be an entrepreneur in the context of personal attitude, the approach to the entrepreneurial career, the approval of being an entrepreneur and entrepreneurial culture the context of social norms, and the personal competence factors in the context of perceived behavior control were found to be meaningful and associated with entrepreneurship intention. On the other hand, entrepreneurship education factors were found to be related to entrepreneurship intention in linear regression, but not in multiple regression. For this reason, the relationship of education with attitude toward behavior, perceived behavior control, and subjective norms was also investigated. According to the results, entrepreneurship education was found to be correlated with the attraction to be an employee and the attraction to be an entrepreneur in the context of personal attitude. The relationship with perception of entrepreneurial career and approval of being an entrepreneur is found in the context of subjective norm. In the context of perceived behavior control, it has been found to be related to personal competence and personal skill.TABLE OF CONTENTSÖZETiABSTRACTiiiACKNOWLEDGEMENTSvLIST OF TABLESviiiLIST OF FIGURESxiABBREVATIONSxii1. INTRODUCTION11.1. Definition of Core Concept11.2. The Importance of Entrepreneurship21.3. Need for Research21.4. The Purpose of The Study31.5. Organization of Dissertation32. LITERATURE REVIEW42.1. The Definitions and Historical Development of Entrepreneurship42.2. Entrepreneurship in Turkey72.3. Entrepreneurial Intention92.4. Factors Affecting Entrepreneurial Intention102.4.1. Demographic Factors102.4.2. Psychological Characteristics132.4.3. Entrepreneurship Education152.4.4. Entrepreneurial Intention Models172.5. Research on Entrepreneurial Intention233. METHODOLOGY AND RESEARH DESIGN323.1. The Scope of The Research323.2 The Proposed Theoretical Research Model333.3. Research Questions343.4. Sample and Data Collection344. RESEARCH AND FINDINGS374.1. Reliability and Factor Analyses374.1.1. Reliability and Factor Analysis of Attitude Toward Behavior384.1.2. Reliability and Factor Analysis of Subjective Norms414.1.3. Reliability and Factor Analysis of Perceived Behavioral Control434.1.4. Reliability and Factor Analysis of Entrepreneurship Education464.1.5. Reliability and Factor Analysis of Entrepreneurial Intention484.2. Revised Model and Hypotheses After the Reliability and Factor Analyses514.3. Correlation and Simple Linear Regression Analyses534.4. Correlations and Multiple Regression Analyses644.5. Independent t-Test Analyses of Demographic Data694.6. ANOVA Analyses of Demographic Data724.7. Results834.7.1. Results of Factor and Reliability Analyses834.7.2. Results of The Simple Linear Regression for Entrepreneurial Intention844.7.3. Results of The Simple Linear Regression for The Effect of Entrepreneurship Education854.7.4. Results of Multiple Linear Regression for Entrepreneurial Intention864.7.5. Results of Independent t-Tests for Entrepreneurial Intention864.7.6. Results of ANOVA Tests for Entrepreneurial Intention875. DISCUSSIONS AND CONCLUSIONS885.1. Discussions and Implications885.2. Conclusion935.3. Limitations935.4. Recommendations946. REFERENCES95APPENDIX: QUESTIONNAIRE104
Keywords: Business; Entrepreneurship Education; Entrepreneurship Event Model; Entrepreneurship Intention; Girişimcilik; Girişimcilik Eğitimi; Girişimcilik Olayı Modeli Entrepreneurship; Girişimcilik Yönelimi; İşletme; Planlanmış Davranışlar Teorisi; Planned Behavior Theory